Developing critical reflective thinking among church leaders in sub-Saharan Africa - Rev. Charles E. Kingsbury (Adult Education Research Conference, 1996)
The author summarizes the current state of Church leadership development programs in sub-Saharan Africa. His pilgrimage of moving from "banking" to praxis teaching is related. The need for training for teachers in such programs is explored and initial results from a pilot program are given. Positive changes in the Church resulted. A model for the diffusion of this type of teaching is proposed.